2001
DOI: 10.1046/j.1365-2141.2001.02716.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐prothrombin antibodies: assay conditions and clinical associations in the anti‐phospholipid syndrome

Abstract: Anti‐phospholipid antibodies (aPL) are associated with an increased risk of thrombosis and recurrent fetal loss. Antibodies to prothrombin (aPT) have been associated with the anti‐phospholipid syndrome (aPS). We assessed variations in aPT assay methodology to optimize an aPT method that was used to screen patients with aPS (n = 66). Detection of aPT using enzyme‐linked immunosorbent assay was influenced by the concentration of the capture antigen, the microtitre plate type and the buffer system. The combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
3
29
0
1
Order By: Relevance
“…All the MAHS contain keratoprotein, and they were reported with many bioactivities, such as anticoagulation effect (Kim et al, 2004), antithrombotic effect (Kim et al, 2004), anti-fever effect (Hu et al, 2006), and anti-inflammatory effect (Sun, 2004). Anticoagulation and antithrombotic effects, which are two main bioactivities, were evaluated by classic means of plasma recalcification time (Dragoni et al, 2001), thrombin time (Donohoe et al, 2001), thrombin consumption (PPRC, 2010), thrombus in vitro (Desai, 2004) and whole blood-gore (Rand et al, 1996), so as to provide theoretical reference for the exploitation of the substitutes. We believe that with further efforts and judicious guide, people will finally accept the substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…All the MAHS contain keratoprotein, and they were reported with many bioactivities, such as anticoagulation effect (Kim et al, 2004), antithrombotic effect (Kim et al, 2004), anti-fever effect (Hu et al, 2006), and anti-inflammatory effect (Sun, 2004). Anticoagulation and antithrombotic effects, which are two main bioactivities, were evaluated by classic means of plasma recalcification time (Dragoni et al, 2001), thrombin time (Donohoe et al, 2001), thrombin consumption (PPRC, 2010), thrombus in vitro (Desai, 2004) and whole blood-gore (Rand et al, 1996), so as to provide theoretical reference for the exploitation of the substitutes. We believe that with further efforts and judicious guide, people will finally accept the substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Several studies have been published with regard to the relationship between the presence of aPT-A and APS-related clinical features with conflicting conclusions. [8][9][10][11][12][13][14][15][16][17][18][19][20] A recent systematic review suggested that both antibodies against prothrombin, aPT-A and aPS/PT, are risk factors for thrombosis, but that aPS/PT represent a stronger risk factor for arterial and/or venous thrombosis when compared to aPT-A. 21 In two prospective studies, the presence of aPT-A has been reported as a predictor of thromboembolic events in patients with aPL, mainly in those patients positive for LA.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is inherent heterogeneity of APLAs and yet unresolved problems with assay standardization for both the classic assays for LAs and ACLAs as well as for anti-␤2-GP-I or anti-PT. [12][13][14][15][16] Third, studies did not discriminate between persistent and transient APLA subtypes, which is another means of discriminating pathogenic from benign APLAs. 17,18 We have previously reported a highly significant association of presence of LAs with TEs in pediatric patients with SLE.…”
Section: Introductionmentioning
confidence: 99%